Nepalese malacology trails behind - Budha, Prem B (Himalayan Journal of Sciences, 2007)
Mollusks of the world are, in general, more thoroughly documented than other invertebrates. This is the case for the Himalayas as well – except in Nepal. A scant 139 species have been reported from Nepal, but the new sightings reported every year and the high percentage of endemism (94.6 for terrestrial and 47.8 for aquatic mollusks) both suggest that a focused and accelerated study of these creatures is warranted. However, inauspicious externalities indicate that, for the foreseeable future, progress is unlikely to exceed the proverbial snail’s pace. Himalayan Journal of Sciences 3(5) 2005 p.9-10